Analysis of hybrid stepper motor performance under the influence of voltage supply interference - Salami, Abdulazeez F.; Adetunji, Lawal Wahab; Khan, Sheroz; Gunawan, Teddy Surya; Jarot, Sigit Puspito Wigati (IIUM Press, 2011)
This chapter investigates the effects of voltage supply interference on the performance of hybrid stepper motor. MATLAB Simulink is used to model the power supply, sinusoidal interfering signal, stepper motor driver circuit and the hybrid stepper motor. This stepper motor is using a DC Voltage supply of 28 volts and it is a two-phase motor with a step angle of 1.80 • The different simulation scenarios that is explored in this work are for a noiseless power.